Knowledge, attitude, and practices of infection prevention and control among radiographers in a resource constraint setting in Namibia - Wako Dihako; Mondjila Amkongo; Abel Karera; Moneni Shilumba (AOSIS, 2023)
Background: Radiographers' role as healthcare workers places them at constant risk for hospital-acquired infections. Practical, evidence-based methods are necessary to reduce the transmission of pathogens to and from patients and healthcare workers. Objectives: The main objectives of this study were to determine knowledge, attitude, and practice levels regarding infection prevention and control (IPC) strategies among radiographers in Windhoek and Oshakati, and measure their relationships with other variables. Methods: A quantitative descriptive design was employed. To assess the knowledge, attitude, and practice levels among radiographers, a self-administered questionnaire was used. Twenty-seven radiographers took part in the study, producing a 68% response rate. Results: The study revealed that the majority of the radiographers showed an appropriate level of overall knowledge and attitude toward infection prevention and control. However, the majority of their practice levels were poor. Pearson rank correlation test revealed that the radiographers' knowledge was significantly associated with attitudes (P= 0.004; r=0.53) and practices (P=0.03; r=-0.41) with a moderate positive and negative correlation, respectively. Conclusions: In conclusion, the study revealed that radiographers are knowledgeable about IPC strategies, and have good attitudes toward them. However, their practice was poor and inconsistent with the level of knowledge demonstrated. Therefore, it is recommended that healthcare service managers establish efficient and rigorous means of monitoring adherence to IPC strategies and improving practices to reduce incidences of health-acquired infections among radiographers, especially in the age of a pandemic.